Safety, immunological effects and clinical response in a phase I trial of umbilical cord mesenchymal stromal cells in patients with treatment refractory SLE. Issue 1 (12th July 2022) - Kamen, Diane L; Wallace, Caroline; Li, Zihai; Wyatt, Megan; Paulos, Crystal; Wei, Chungwen; Wang, Hongjun; Wolf, Bethany J; Nietert, Paul J; Gilkeson, Gary
Abstract : Background: Reports of clinical improvement following mesenchymal stromal cell (MSC) infusions in refractory lupus patients at a single centre in China led us to perform an explorative phase I trial of umbilical cord derived MSCs in patients refractory to 6 months of immunosuppressive therapy. Methods: Six women with a SLEDAI >6, having failed standard of care therapy, received one intravenous infusion of 1×10 6 MSCs/kg of body weight. They maintained their current immunosuppressives, but their physician was allowed to adjust corticosteroids initially for symptom management. The clinical endpoint was an SRI of 4 with no new British Isles Lupus Activity Guide (BILAG) As and no increase in Physician Global Assessment score of >0.3 with tapering of prednisone to 10 mg or less by 20 weeks. Results: Of six patients, five (83.3%; 95% CI 35.9% to 99.6%) achieved the clinical endpoint of an SRI of 4. Adverse events were minimal. Mechanistic studies revealed significant reductions in CD27IgD double negative B cells, switched memory B cells and activated naïve B cells, with increased transitional B cells in the five patients who met the endpoint. There was a trend towards decreased autoantibody levels in specific patients. Two patients had increases in their Helios+Treg cells, but no other significant T cell changes were noted. GARP-TGFβ complexes were significantly increased following the MSC infusions. The B cell changes and the GARP-TGFβ increases significantly correlated with changes in SLEDAI scores. Conclusion: This phase 1 trial suggests that umbilical cord (UC) MSC infusions are very safe and may have efficacy in lupus. The B cell and GARP-TGFβ changes provide novel insight into mechanisms by which MSCs may impact disease. Trial registration number: NCT03171194 .